HUBUNGAN KEHARMONISAN KELUARGA TERHADAP RISIKO PENYALAHGUNAAN NAPZA PADA - Dewi, Eka Trisnawati; Jumaini, Jumaini; Herlina, Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Family harmony has something to do with mental health, especially with the risk of drug abuse. This study aims todetermine the relationship between family harmony and risk of drug abuse to adolescents in Satu Atap Teluk KenidaiState Junior High School with a descriptive research design and a correlation cross sectional approach. There were 81respondents as the samples of the research. They were taken based on the inclusion criteria using the total samplingtechnique. The measuring tool used was a set of questionnaire that has been tested for its validity and reliability. Theanalyses used were univariate analysis in order to know the frequency distribution and bivariate analysis using chisquaretest. The statistical test resulted in a P value of (0.000) < (0.05) which means there is a significant relationshipbetween family harmony and risk of drug abuse to adolescents in Satu Atap Teluk Kenidai State Junior High School. Theresult of research showed that family harmony was not the main factor of drug abuse but there were other factors suchas peer group, chance and school environment, so this research is expected to be the teenagers' concern and they haveto be more selective in choosing friends and a good environment. Finally, they are supposed to be able to protectthemselves in order not to be easily affected by peers or communities which are not expected.Keywords: Adolescents, Family Harmony, Risk of Drug Abuse